Pemanfaatan Quiziz sebagai Media Pembelajaran Bahasa Indonesia di SMK Ulumul Fata - Hamdan, Fauzul (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
It is important for a teacher to be able to utilize technology in learning, especially in today's digital era. One of the uses of technology in education is through the application Quizizz. Quizizz is a game-based application that can be utilized as a medium for learning the Indonesian language. Quizizz can capture students' attention in receiving Indonesian language learning materials at SMK Ulumul Fata. This article aims to describe the utilization of Quizizz as a learning medium for the Indonesian language at SMK Ulumul Fata. Through a qualitative approach, data collection was carried out by observing media usage, interviewing teachers, and reviewing relevant reference sources. The results of the research show that the use of Quizizz at SMK Ulumul Fata has a positive impact on student engagement in learning, enhances student motivation in understanding the material, and fosters positive perceptions among students and teachers regarding Indonesian language learning.